2020
DOI: 10.3171/2019.6.jns19541
|View full text |Cite
|
Sign up to set email alerts
|

First application of 7-T ultra–high field diffusion tensor imaging to detect altered microstructure of thalamic-somatosensory anatomy in trigeminal neuralgia

Abstract: OBJECTIVETrigeminal neuralgia (TN) is a debilitating neurological disease that commonly results from neurovascular compression of the trigeminal nerve (CN V). Although the CN V has been extensively studied at the site of neurovascular compression, many pathophysiological factors remain obscure. For example, thalamic-somatosensory function is thought to be altered in TN, but the abnormalities are inadequately characterized. Furthermore, there are few studies using 7-T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
5
11
0
Order By: Relevance
“…That being said, there is neuroanatomical evidence that the smaller, ipsilateral dorsal trigeminothalamic tract containing non-decussating bers may be implicated in orofacial pain 31 , and recent in vivo tractography results show ipsilateral thalamo-cortical diffusivity abnormalities in TN. 18 Our current observations add to these ndings, and further link surgical response to bilateral, system-wide changes in the trigeminal system.…”
Section: Discussionsupporting
confidence: 70%
“…That being said, there is neuroanatomical evidence that the smaller, ipsilateral dorsal trigeminothalamic tract containing non-decussating bers may be implicated in orofacial pain 31 , and recent in vivo tractography results show ipsilateral thalamo-cortical diffusivity abnormalities in TN. 18 Our current observations add to these ndings, and further link surgical response to bilateral, system-wide changes in the trigeminal system.…”
Section: Discussionsupporting
confidence: 70%
“…The association among TN, migraine, cluster headache, and low back pain in epidemiology and pathogenesis has been acknowledged [25][26][27]. Thalamic-somatosensory dysfunction and dysrhythmia have been proved to be associated with TN, migraine and low back pain, and the abnormal functional connectivity between the thalamus and attentional cerebral networks has been substantially proved at rest during migraine attacks [10,[28][29][30][31]. With regard to the PCC, it play an important role in pain modulation, and has been considered as crucial brain regions of default mode network (DMN) [32].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent voxel-based morphometry (VBM) studies [9], the TN group showed significantly decreased gray matter volume in the bilateral superior/ middle temporal gyrus (STG/MTG), bilateral parahippocampus, left anterior cingulate cortex (ACC), caudate nucleus, right fusiform gyrus, and right cerebellum compared with the HC. In addition to GM volume deficits, alterations of WM integrity in the thalamicsomatosensory tract ipsilateral to the site of NVC was reduced in CTN patients via topographical analysis [10].…”
Section: Introductionmentioning
confidence: 95%
“…Decreased myelination at the proximal pontine segment was correlated with poor response to treatment in patients with MS-TN ( Li et al, 2019 ). In 2019, microstructural alterations were observed in the thalamic-somatosensory tracts of patients with TN ( Rutland et al, 2019 ). Moreover, a decrease in FA of the thalamic-somatosensory tract ipsilateral to the site of neurovascular compression was observed, while MD and RD were increased ipsilaterally in 10 patients with TN when compared with the control group.…”
Section: Diffusion Tensor Tractography For Diagnosis Of Various Types Of Neuropathic Painmentioning
confidence: 99%